STRATEGIC PLANNING FOR EFFECTIVE MANAGEMENT OF CITIZENSHIP EDUCATION IN SCHOOLS - Dadang Mulyana (Sean Institute, 2022)
Citizenship education has a crucial role in shaping students' attitudes, values and active participation in national and state life. Even though it is important, the implementation of civic education management still often faces challenges. This research aims to identify, design and evaluate effective strategic planning for the management of citizenship education in the school environment. This research uses a qualitative approach with descriptive methods. The research results show that strategic planning for the management of Citizenship Education in schools has a positive impact. Setting long and short term goals helps shape student character, while developing an integrated and relevant curriculum stimulates learning motivation. Involving parents and the community strengthens students' understanding of civic values, and ongoing training for teachers improves the quality of learning. The use of information and communication technology enriches students' learning experiences, while encouraging students' active participation in extracurricular activities develops leadership skills. Overall, the implementation of these strategies contributes significantly to shaping students' civic character, strengthening the role of schools in forming active citizens, committed to civic values, and ready to participate in community development.